Core-proton coupled nature of the 11/2+ state in 131 Sb probed by lifetime measurements. (1st March 2023) - Bottoni, S.; Gamba, E. R.; De Gregorio, G.; Gargano, A.; Leoni, S.; Fornal, B.; Brancadori, N.; Ciconali, G.; Crespi, F. C. L.; Cieplicka-Oryńczak, N.; Iskra, L. W.; Colombi, G.; et al.
Abstract: The structure of the 11 / 2 1 + state in 131 Sb was investigated at the LOHENGRIN spectrometer of Institut Laue-Langevin via neutron-induced fission of 235 U and lifetime measurements, yielding T 1 / 2 = 3 ( 2 ), at the edge of the sensitivity of the experimental method. This first result for the 11 / 2 1 + state half-life in neutron-rich Sb isotopes provides a quadrupole reduced transition probability to the ground state of B ( E 2 ) = 1.4 − 0.6 + 1.5 W.u., very close to the B ( E 2 ; 2 1 + → 0 1 + ) in 130 Sn. Realistic shell-model calculations reproduce well both the experimental level scheme of 131 Sb and the B ( E 2 ; 11 / 2 1 + → 7 / 2 1 + ) value, indicting a dominant 2 + ( 130 Sn ) ⊗ π g 7 / 2 core-proton coupled configuration for the 11 / 2 1 + state.